Preparation of a monolithic sorbent using a response surface methodology - Li, Xiaoxia; Lee, Yu Ri; Row, Kyung Ho (International Journal of Engineering and Technology, 2016)
A 17-run Box-Behnken Design (BBD) was introduced to optimize the synthesis conditions of a monolithic sorbent. The effects of the amount of monomer (mL), crosslinker (mL) and porogen (mL) were investigated. The experimental data was fitted to a second - order polynomial equation by multiple regression analysis, which was examined using statistical methods. The adjusted coefficient of determination (R2Adj) in this model was 0.9867. The probability value (p<0.0001) revealed the high significance of the regression model. A mean amount of 5057.4 mg polymer was produced under the following optimized synthesis conditions: 0.51 mL monomer, 2.94 mL crosslinker and 2.84 mL porogen. The actual experimental result was in good agreement with the predicted model value.